Proceedings of the 3rd International Conference on Banking, Accounting, Management and Economics (ICOBAME 2020) 2020
DOI: 10.2991/aebmr.k.210311.012
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Financial Performance of English Football Clubs: Arsenal and Manchester City

Abstract: Football is a sport and an attractive business with a high turnover of money around it. A football club may earn much from sponsorship, ticketing, and merchandise; however, it may also suffer loss from player transferred. This study aims to analyze the financial statements of professional football clubs in England, namely Arsenal and Manchester City. This study also aims to compare these football clubs' financial performance using the Z-score Altman, Springate, and Zmijewski bankruptcy prediction model. Financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…The prediction is necessary for management, owners, and investors to prepare for any potential financial issues. Most businesses that go bankrupt do have a substantial impact on their employees, investors, and other stakeholders in their operations, in addition to the firm itself (19,20).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The prediction is necessary for management, owners, and investors to prepare for any potential financial issues. Most businesses that go bankrupt do have a substantial impact on their employees, investors, and other stakeholders in their operations, in addition to the firm itself (19,20).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This development towards incorporation has also led to an increase in academic publications on the financial structures and financial performances of clubs. While some studies on football clubs examine athletic performance and financial performance together (Alaminos et al, 2020;Dimitropoulos and Limperopoulos, 2014;Galariotis et al, 2018;Güngör, 2014;Kırkulak Uludağ and Sigalı, 2016;Panagiotis, 2009;Pinnuck and Potter, 2006;Plumley et al, 2017;Rey and Santelli, 2017;Sakinc et al, 2017), some other studies focused only on financial performance (Ecer and Boyukaslan, 2014;Güleç et al, 2019;Guzmán, 2006;Ika et al, 2020;Karadeniz et al, 2014;Sakınç, 2014). Dimitropoulos (2009), as a result of their study using regression analysis in the Greek Football League between 1994 and 2004, suggested that the profitability of the football league was positively affected by the short-term success of the clubs, but not by the long-term success and the uncertainty of the football league.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature, there are academic studies examining the financial performance of football clubs in different leagues using various techniques. E.g., models and ratio analysis used to measure financial failure (Güleç et al, 2019;Ika et al, 2020;Karadeniz et al, 2014), regression analysis (Panagiotis, 2009;Rey and Santelli, 2017), neural networks (Alaminos et al, 2020;Güngör, 2014), event analysis (Kırkulak Uludağ and Sigalı, 2016), panel data analysis ( (Dimitropoulos and Limperopoulos, 2014) and among multi-criteria decision making techniques Data Envelopment Analysis (Guzmán, 2006), PROMETHEE II (Galariotis et al, 2018), TOPSIS (Sakinc et al, 2017), Grey Relational Analysis (GRA) (Ecer and Boyukaslan, 2014;Oral, 2016;Sakınç, 2014). In this study, unlike other studies, a method integrating Criteria Importance Through Intercriteria Correlation (CRITIC) and GRA techniques was used.…”
Section: Introductionmentioning
confidence: 99%
“…A good profitability ratio is positive information for investors from the perspective of the profits to be obtained, so that it will affect the investment decisions of investors. So that will have an effect on stock (Ika et al, 2021). The demand and supply of soccer shares occur due to the existence of good information signals about the company's profits so that it has an influence on investors' profit expectations on their investments, which in turn will have an impact on the soccer club's stock price (Sumantri & Agustianti, 2017)…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The initial demand for shares exceeded the offer, so that the initial offering of Bali United shares was oversubscribed (Pradhan et al, 2017) .Another opinion about the football industry is that many European football clubs are in trouble with debt so that they go bankrupt. Factors that allow this to happen are expenditures on purchasing new players, player salaries, coach salaries, building stadiums and so on (Ika et al, 2021) The phenomenon above gives speculation that not all football clubs have managed to survive in market share. An indicator of the success of a company can be reflected in the stock price, where there is a sale and purchase transaction of shares reflecting the strength of an industry's market share on the stock exchange.…”
Section: Introductionmentioning
confidence: 99%